Quasianalytic classes of functions on a plane - Maimeskul, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Quasianalytic classes of functions in a Jordan domain G are defined. We consider classes of functions defined by conditions imposed on the decrease rate of the best uniform polynomial approximations and investigate the dependence of the quasianalyticity of these classes on the geometric structure of a domain.